Ecosystems Services Provided by Bats Are at Risk in Brazil - Brasileiro, Lais A. M.; Machado, Ricardo B.; Aguiar, Ludmilla M. S. (Frontiers in Ecology and Evolution, 2022)
Ecosystem services (ES) are essential for human society worldwide. ES originate from ecological processes commonly occurring in well-preserved regions. Bats play an essential role in providing such services, primarily insect suppression, plant pollination, and seed dispersal. Human activities have affected Earth’s systems, compromising species and ecosystems and, consequently, the ES provision. Brazil is a country with many bat species but is also one of the world’s leaders in deforestation. Here we aimed to identify regions with high potential for bats ecosystem services provision, assuming that the predicted presence of the species represents the existence of the services. First, we used a Maximum Entropy algorithm to model the distribution of 128 bat species, which correspond to 71% of the Brazilian species. We classify all species into 10 different groups, which resulted from a combination of three body sizes and four predominant trophic guilds (i.e., frugivores, insectivores, nectarivores, and carnivores). The guilds were associated with services of seed dispersion, pest control, pollination, and animal control. Then, we created a 0.5 × 0.5-degree grid to represent an index of ES per guild, which is defined by the sum of the product of the bat’s size weight (1, 2, or 3) by the area occupied of each species in each cell. For comparison, the index was normalized and scaled from 0 to 1. Finally, we used a map of current land use to compare the effects of natural area suppression on the provision of ES in each cell. Our results indicate a substantial reduction in the provision of ES by bats in extensive parts of the central and eastern parts of Brazil, but changes in ES varies among biomes. While the loss of species is an important factor affecting the provision of ES in the Atlantic Forest and the Cerrado, the reduction of species occurrence is most important factor in Amazonia, Caatinga, or Pantanal regions. We suggest that degraded area restoration should be promoted in areas with high ES values and areas near cities and croplands and that a precautionary approach of promoting the conservation of high provider richness should be applied to protect the continuation of bat’s ES.